Studies on Saline and Alkaline Soils and their Possible Improvement by Affrestation - Yadav, J.S. P.; Pathak, T.C. (Journal of Soil and Water Conservation, 2022)
The saline and alkaline soils, which are estimated to occupy an extensive area of approximately 15 to 20 million acres in India, still remain a baffling problem of paramount economic importance owing to their unfavourable physical and chemical characteristics. These soils are widely spread extending from Gangetic plain in north to several States in south including considerable area of predominantly saline soils in the coastal belts adjoining the sea and in the estuaries of numerous rivers of the peninsula. They are generally found in patches, but even contiguous blocks are met with in some places. Soil conservation should aim at mitigating the harmful effects of those factors which have brought about their deterioration and to make their best possible use through well-planned management.